La fotografía publicitaria en el sector gastronómico de Babahoyo como estrategias de promoción - Contreras Vera, Geovany Joel (2021)
This case study performs an in-depth analysis of advertising photography in the gastronomic sector in the city of Babahoyo, it is based on making known how some local restaurant owners use this advertising method as a promotional strategy. In a way, it reveals the laso of marketing, food photography and photographic advertising. Techniques such as indirect observation, interview and questionnaire will be used, these skills will be applied to restaurant owners such as; "Chingana Montuvia", "Riola Bar", "Papéate". Places where objective data of relevance will be obtained on why it is important for them to use photo advertising in their businesses, and how it affects the effect of it on consumers. Through this research, various characteristics and relevant reviews about advertising strategies and global definitions of photography, advertising, gastronomy, and other topics of business interest will be exposed. Offer a method that is helpful to those who are in charge of 'a dining room, and that these serve as an example for future mini-entrepreneurs who want to start a restaurant in the Babahoyo canton.